Complexity of mathematics - Martínez Suárez, Alexander (Innovaciencia, 2017)
Introduction: This article studies the process of mathematics over the years: its transformations and new proposals related to transdisciplinarity and how to solve problems; aspects that become consolidated fundamental axes from which itis possible to advance scientifically and in different dimensions. Materials and methods: It is a reflective article that allows us to think about the different outstanding changes in mathematics, it is important to highlight the considerable and significant progress in the development of a mathematics different from the traditional one, complex from relation to the whole. Results and Discussion: A collection of information by different authors and periods that show the center of study for the moment, is allowed to publicize the development of the mathematics of the complexity “commonly called”, and how it has been taking more recognition for its involvement and application. Conclusions: In this sense, it creates a new form of science that is more oHpen, more participatory than the different phenomena and situations of modeling, managing to get out of the traditional crossroads in which it has always been considered.